Protein succinylome analysis identifies citrate synthase as a central regulator of osteoclast metabolic activity - Yu, Dayoung; Gao, Yue; Luzarowski, Marcin; Seebach, Elisabeth; Heitkamp, Thomas; Börsch, Michael; Ruppert, Thomas; Hieke-Kubatzky, Katharina (The FEBS journal, 2025)
Tumour necrosis factor ligand superfamily member 11 (TNFSF11; RANKL) and macrophage colony-stimulating factor 1 receptor (M-CSF) differentiate macrophages into osteoclasts. This process is characterised by changes in metabolic activity that support energy-consuming processes. Treatment with RANKL triggers a phenotype of accelerated metabolism with enhanced glycolysis and an initial disruption of the tricarboxylic acid cycle (TCA) through increased expression of the enzyme aconitate decarboxylase (ACOD1), which results in an upregulation of intracellular succinate levels. Succinate then causes post-translational succinylation of lysine residues. ACOD1 as an inducer of protein succinylation and the desuccinylase NAD-dependent protein deacylase sirtuin-5, mitochondrial (SIRT5) are regulated differentially, and the initially high expression of ACOD1 decreases towards the end of differentiation, whereas SIRT5 levels increase. To mimic the effect of protein succinylation, diethyl succinate or a SIRT5 inhibitor was added during differentiation, which reduced the formation of large osteoclasts, showing its relevance for osteoclastogenesis. To identify succinylated proteins, we used an immunoaffinity-based liquid chromatography-tandem mass spectrometry (LC-MS/MS) approach. Most lysine succinylated proteins were mitochondrial metabolic enzymes. Citrate synthase (CS), the enzyme catalysing the first reaction of the TCA cycle, showed a notable difference in succinylation levels before and after RANKL stimulation, with succinylation detected exclusively in stimulated cells. Immunoprecipitation assays confirmed CS succinylation. Using whole cell extracts, we observed that RANKL treatment decreased CS activity in a concentration-dependent manner. This suggests that CS could be critical in the context of energy production during osteoclastogenesis and that protein succinylation modulates the differentiation program of osteoclasts.
Online veröffentlicht: 2. April 2025
Gesehen am 15.10.2025